2012
DOI: 10.1016/j.jad.2012.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol responses to psychosocial stress predict depression trajectories: Social-evaluative threat and prior depressive episodes as moderators

Abstract: Background Alterations of hypothalamic-pituitary-adrenal (HPA) function are well-established in adults with current depression. HPA alterations may persist into remission and confer increased risk for recurrence. Methods A modified version of the Trier Social Stress Test (TSST) was administered at baseline to 32 young adults with remitted major depressive disorder and 36 never-depressed controls. Participants were randomly assigned to either a ‘high–stress’ condition involving social evaluation or a ‘low-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 45 publications
7
55
0
Order By: Relevance
“…The significant correlations observed between salivary cortisol levels and perceived stress, anxiety and depression are in line with previous findings (Morris, Rao, & Garber, 2012) and reinforce the knowledge of the association between psychological and psychophysiological activities. However, while we observed significant changes in cortisol release following CBT, there were no corresponding changes in psychometric scores.…”
supporting
confidence: 91%
“…The significant correlations observed between salivary cortisol levels and perceived stress, anxiety and depression are in line with previous findings (Morris, Rao, & Garber, 2012) and reinforce the knowledge of the association between psychological and psychophysiological activities. However, while we observed significant changes in cortisol release following CBT, there were no corresponding changes in psychometric scores.…”
supporting
confidence: 91%
“…For example an enhanced cortisol response to the TSST has been shown to predict depressive symptoms in young adults (Morris et al, 2012) and suicidal ideation in female adolescents with a history of mental health concerns (Giletta et al, 2014). The results are also consistent with evidence showing greater cortisol reactivity to the TSST in older adults subjected to separation from both parents during childhood (Pesonen et al, 2010) and in young adults exposed to severe pre-natal stress (Entringer et al, 2009).…”
Section: Insert Table 2 Heresupporting
confidence: 65%
“…This may provide an eventual route to allostatic overload and negative physical and mental health outcomes (McEwen, 2000;Morris et al, 2012). It may also underpin observed aberrant diurnal profiles of cortisol secretion in anxious attachment style (Oskis et al, 2011;Quirin et al, 2008).…”
Section: Insert Table 2 Herementioning
confidence: 99%
“…These stress-responses may have less to do with learned reactions to stress and coping styles than with genetically determined biochemical responses which describe a stress-sensitivity (109,180,181). It has been suggested that exposure to major negative life events can activate genetic risks for child and adolescent depression (182).…”
Section: Stressmentioning
confidence: 99%
“…However, contrary to the evidence above about conflict, a recent analysis of data from the Minnesota Twin study suggested that life stressors outside the family (so excluding divorce) were more likely to be associated with internalising disorders at age 17 than were problematic parent relationships (178). Similarly, other studies have associated stressful life events beyond the family with drinking among adolescents with depression (179), and childhood trauma appears to account at least partially for comorbid anxiety and alcohol problems in adolescence (155).These stress-responses may have less to do with learned reactions to stress and coping styles than with genetically determined biochemical responses which describe a stress-sensitivity (109,180,181). It has been suggested that exposure to major negative life events can activate genetic risks for child and adolescent depression (182).…”
mentioning
confidence: 97%